Multisided media markets: Applying the theory of multisided markets to media markets - Nadine Lindstädt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
Media markets recently have been identified as multisided markets. The application of the theory of multisided markets provides a better understanding of such markets. It enriched the hitherto economic approach and led to new insights and perspectives especially for the antitrust authorities when evaluating competition constraints and mergers. This paper reviews the theory of multisided markets and subsequently applies it to media markets. Finally the paper draws attention to the new perspectives and insights the theory provides but also brings open research questions to light.
Keywords: L82; A20; L13; M21; 330; media economics; two-sided markets; multisided platforms; competition; Mediensektor; Medienökonomik; Marktstruktur; Netzwerkökonomik; Theorie